2023
DOI: 10.1093/brain/awad362
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic inflexible learning dynamics explain deficits in depression and schizophrenia

Hans Kirschner,
Matthew R Nassar,
Adrian G Fischer
et al.

Abstract: Deficits in reward learning are core symptoms across many mental disorders. Recent work suggests that such learning impairments arise by a diminished ability to use reward history to guide behaviour, but the neuro-computational mechanisms through which these impairments emerge remain unclear. Moreover, limited work has taken a transdiagnostic approach to investigate whether the psychological and neural mechanisms that give rise to learning deficits are shared across forms of psychopathology. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…97 healthy young adults completed the probabilistic learning task (Figure 2) (Fischer & Ullsperger, 2013;Jocham et al, 2014;Kirschner et al, 2022;Kirschner et al, 2023) on three separate sessions, an initial drug-free session, and after PL and MA. The study followed a double-blinded cross-over design, whereby 50% of participants received MA first, and 50% of participants PL first.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…97 healthy young adults completed the probabilistic learning task (Figure 2) (Fischer & Ullsperger, 2013;Jocham et al, 2014;Kirschner et al, 2022;Kirschner et al, 2023) on three separate sessions, an initial drug-free session, and after PL and MA. The study followed a double-blinded cross-over design, whereby 50% of participants received MA first, and 50% of participants PL first.…”
Section: Resultsmentioning
confidence: 99%
“…To study learning dynamics participants completed a reversal variant of an established probabilistic learning task (Fischer & Ullsperger, 2013;Jocham et al, 2014;Kirschner et al, 2022;Kirschner et al, 2023). Participants completed the task three times: in a baseline session without drug, and after PL and after oral MA (20 mg) administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of research suggests that dopamine modulates striatal coding of prediction errors to enable learning ( Pessiglione et al, 2006 ; Glimcher, 2011 ; Schlagenhauf et al, 2013 ; Schultz, 2016 ; Basanisi et al, 2023 ). Imaging studies in human schizophrenic participants have reported striatal dysfunction during learning ( Schlagenhauf et al, 2014 ; Katthagen et al, 2020 ) and aberrant learning from feedback accompanied by altered EEG correlates ( Kirschner et al, 2024 ). In monkeys, midbrain dopamine neurons have been found to code reward size but also uncertainty or confidence during perceptual decision-making ( de Lafuente and Romo, 2011 ; Lak et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%